USB 25-MEMBER DELEGATION PAYS COURTESY CALL TO USM - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, May 2015 Universiti Sains Malaysia (USM) recently hosted a courtesy call from a Universitas Sulawesi Barat (USB) 25member delegation led by the Deputy Rector of Academic and Student Affairs, Dr Muhammad Saad.